Penerapan Sanksi Pidana Terhadap Residivis Pada Penyalahgunaan Narkotika Di Kabupaten Batang (Studi Putusan Nomor 44/PID.SUS/2023/PNBTG) - Moch Ya'lu Bastomi; Wenny Megawati (LPPM Universitas Ekasakti Padang, 2023)
Drug abuse is a serious problem in society, especially among the younger generation. In law enforcement related to narcotics abuse, it is necessary to increase supervision and control in order to prevent and eradicate this crime. Decision Number 44/PID.SUS/2021/PN BTG is an example of drug abuse against recidivists. The research uses normative juridical research methods and a qualitative approach. The results of the study discuss the application of criminal sanctions for drug abuse recidivists in Decision Number 44/Pid.Sus/2021/PN The judge imposed a prison sentence of 5 years and a fine of Rp. 1,000,000,000. The evidence was confiscated and destroyed except for the returned motorcycle. Juridical, sociological, and philosophical considerations were used in the decision. The purpose of imprisonment is deterrent effect and protection of society. This decision reflects the judges' consideration of juridical, sociological, and philosophical aspects in applying criminal sanctions. Decision Number 44/Pid.Sus/2021/PN Btg against M. Wahyu Wijayanto Alias Anto Bin (Alm.) Kayun Wibowo shows that the defendant was legally proven to have committed the crime of being an intermediary in the sale and purchase of class I narcotics. The defendant admitted to abusing drugs twice in 2022. The judge sentenced the defendant to 5 years imprisonment and a fine of Rp 1,000,000,000, with the provision of 1 month imprisonment if the fine is not paid. The evidence, except for the motorcycle, was destroyed. The defendant is also required to pay court costs of Rp. 5,000.